2021
DOI: 10.3390/biology10090883
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Introductions of Rabbit Hemorrhagic Disease Virus Lagovirus europaeus/GI.2 in Africa

Abstract: Rabbit hemorrhagic disease (RHD) causes high mortality and morbidity in European rabbits (Oryctolagus cuniculus). In Africa, the presence of the causative agent, the rabbit hemorrhagic disease virus (RHDV), was first confirmed in 1992 (genotype Lagovirus europaeus/GI.1). In 2015, the new genotype Lagovirus europaeus/GI.2 (RHDV2/b) was detected in Tunisia. Currently, GI.2 strains are present in several North and Sub-Saharan African countries. Considerable economic losses have been observed in industrial and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In agreement with our findings, it has been reported that GI.2 strains induced, at least, 80% mortality ( 45 ). Moreover, in this study, RHDV positive samples were collected from rabbits at different ages and sexes, thereby contributing to confirm that GI.2 infects male and female rabbits at all ages ( 5 , 6 , 8 , 19 , 33 , 46 ).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In agreement with our findings, it has been reported that GI.2 strains induced, at least, 80% mortality ( 45 ). Moreover, in this study, RHDV positive samples were collected from rabbits at different ages and sexes, thereby contributing to confirm that GI.2 infects male and female rabbits at all ages ( 5 , 6 , 8 , 19 , 33 , 46 ).…”
Section: Discussionmentioning
confidence: 75%
“…Analysis of the VP60 ML tree revealed that all Algerian strains clustered within the strongly supported GI.2 group (bootstrap value 100), but they were further distributed into two distinct clusters. Indeed, the strain Algeria 002 grouped with the Tunisian GI.2 strains isolated from 2018 to 2020 (bootstrap value of 99) ( 33 ). The remaining six strains isolated between 2020 and 2021 (Algeria 024, 027, 052, 068, 076, and 083) appeared closely related to North American GI.2 strains (from 2020 to 2021; bootstrap value of 99.8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In New Zealand and Australia, where rabbits are considered an agricultural pest, the virus was released intentionally as a means of biological population control, where it reduced the population by nearly 95% [ 4 ]. In 2010, a novel strain of the virus, referred to as RHDV GI.2 or RHDV2, emerged in France and has since spread globally to nearly every continent, including Europe, Asia, Australia, Africa, and North America [ 5 , 6 , 7 , 8 , 9 ]. The original virus responsible for RHD, now called RHDV G1.1 or RHDV, has a high mortality rate in European rabbits ( Oryctolagus cuniculus ) but typically does not cause disease in other lagomorph species, while RHDV2 has a much broader host range, with documented infections in a variety of wild lagomorphs, including cottontails ( Sylvilagus spp.)…”
Section: Introductionmentioning
confidence: 99%
“…In January 2014, a strain of RHDV2 was found in dead rabbits vaccinated against RHDV in Australia, representing a transoceanic transmission of RHDV2 from Europe to Australia [ 14 ]. In February 2015, RHDV2 spread to Tunisia [ 15 ], the northernmost country in Africa, separated from Europe by the sea. In 2017, cases of RHDV2 were also reported in Morocco [ 16 ], an African country across the sea from Spain.…”
Section: Introductionmentioning
confidence: 99%